Managing accidental hypothermia: a UK-wide survey of prehospital and search and rescue providers. Issue 11 (19th July 2018) - Freeman, Samuel; Deakin, Charles D; Nelson, Magnus J; Bootland, Duncan
Abstract : Aim: The management of hypothermic casualties is a challenge faced by all prehospital and search and rescue (SAR) teams. It is not known how the practice of these diverse teams compare. The aim of this study was to review prehospital hypothermia management across a wide range of SAR providers in the UK. Methods: A survey of ground ambulances (GAs), air ambulances (AAs), mountain rescue teams (MRTs, including Ministry of Defence), lowland rescue teams (LRTs), cave rescue teams (CRTs), and lifeboats and lifeguard organisations (LLOs) across the UK was conducted between May and November 2017. In total, 189 teams were contacted. Questions investigated packaging methods, temperature measurement and protocols for managing hypothermic casualties. Results: Response rate was 59%, comprising 112 teams from a wide range of organisations. Heavyweight (>3 kg) casualty bags were used by all CRTs, 81% of MRTs, 29% of LRTs, 18% of AAs and 8% of LLOs. Specially designed lightweight (<0.5 kg) blankets or wraps were used by 93% of LRTs, 85% of LLOs, 82% of GAs, 71% of AAs and 50% of MRTs. Bubble wrap was used mainly by AAs, with 35% of AAs reporting its use. Overall, 94% of packaging methods incorporated both insulating and vapour-tight layers. Active warming by heated pads or blankets was used by 65% of AAs, 60% of CRTs, 54% of MRTs, 29% of LRTs and 9% of GAs, with no LLO use. Temperature measurement was reported by all AAs and GAs, 93% of LRTs, 80% of CRTs, 75% of MRTs and 31% of LLOs. The favoured anatomical site for temperature measurement was tympanic. Protocols for packaging hypothermic casualties were reported by 73% of services. Conclusions: This survey describes current practice in prehospital hypothermia management, comparing the various methods used by different teams, and provides a basis to direct further education and research.